MODEL PENGEMBANGAN EKONOMI LOKAL BERDASARKAN CORPOORATE SOSIAL RESPONSIBILITY (CSR) INDUSTRI DI WILAYAH INDUSTRI KOTA CILEGON - Mirajiani Mirajiani; Johan Setiawan; Ari Tresna Sumantri (JURNAL AGRIBISNIS TERPADU, 2019)
The long-term goal of this research is to build local economic strengths that synergize with the growth of sustainable industries in the Cilegon industrial area. The specific target to be achieved is to form a model of an effective and oriented CSR program for community development (short term and long term) that can be a guide / guide to the implementation of CSR of large industrial companies at the local and national level, and formulate a model for local economic development ideal, equitable, and empowering oriented on the basis of industrial CSR. Research is located in the Cilegon Industrial area and carried out using qualitative research methods. The method of data collection is realized by combining triangulation techniques (observation, in-depth interviews and literature studies) with joint study techniques (jisam). The results of the study indicate that the complexity of the form of relations between industry and local communities has led to the implementation of CSR not yet synergizing with the development of the local economy. There are problems with the incompatibility of forms and implementation of CSR programs with the demands of the community